下顎骨中心性に発症した線維性偽腫瘍の1例 - 根岸, 明秀; 岸, 裕子; 信澤, 愛子; 山口, 徹; 横尾, 聡; 笹岡, 邦典 (日本口腔外科学会雑誌, 2012)
Pseudotumor with fibrous proliferation is a rare benign nonneoplastic lesion in the oral region. We report a case of intraosseous fibrous pseudotumor of the mandible. A 50-year-old woman was referred to our university hospital to undergo further evaluation of a radiolucent lesion between the lateral incisor and canine of the right mandible. At presentation, no swelling was found in the alveolus of the anterior region of the mandible. A panoramic X-ray photograph revealed a radiolucent lesion causing root separation of the lateral incisor and canine. A computed tomography scan revealed mild bone swelling, a thinned cortex at the labial side of the mandible, and a low-density mass. Histopathological examination of a biopsy specimen suggested fibrous overgrowth. The lesion was intraorally extirpated under general anesthesia. Histopathological examination of the surgical specimen revealed high-density fibrous proliferation without dysplasia. There was virtually no lymphocyte infiltration. Histopathologically, the lesion was diagnosed to be a fibrous pseudotumor. No recurrence has occurred, and bone regeneration at the extirpated region is good 3 years after surgery.